Concept of data modelling for micro-networks in wine tourism - Hołodnik, Daria; Hernes, Marcin; Rideau, Nicolas; Barbot, Gildas (Koncepcja modelu danych mikrosieci w turystyce winiarskiej, 2021)
The aim of this paper was to develop the concept of a data model for micro-wine tourism networks. “Micro” is used to underline the importance of a perspective of wine tourism experience which was a key determinant for the two presented methods of its design. Thus, in this approach micro-wine tourism networking is defined as a network capability of making dynamic connections corresponding to the creation and delivery of wine activities. The first method is based on obtaning the in-depth knowledge in the studied area, while the second one is related with analytical structuring of the network actors (then called objects) completed by defining their attributes. These attributes were selected due to the significance of creating wine tourism experience. Thus the authores prepared the first conceptual framework of this large-scale design, which provided the structure of the distinguished classes of objects with their attributes.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 3 (61), s. 15-23
Keywords: tourist experience network; wine tourism; data modeling; network dynamics; doświadczenia enoturysty; turystyka winiarska; modelowanie danych; dynamika relacji sieciowych